Merā Walaitī safaranāmā, krita Kamalā Akālī : ika ālocanātamaka adhiaina - Lāmbā, Gobinda Siṅgha, 1929- (Paipasū Buka Ḍipū, 1980)
Study of Merā Walaitī safaranāmā, a chronicle of the 1927 European travels of Kamalā Akālī Lāla Siṅgha, 1889-1977, Panjabi litterateur and religious leader.